Evaluation of acoustic pulse technology as a non-antibiotic therapy for bovine intramammary infections: Assessing bacterial cure vs. recovery from inflammation - Blum, Shlomo Eduardo; Krifuks, Oleg; Weisblith, Limor; Fleker, Marcelo; Lavon, Yaniv; Zuckerman, Alon; Hefer, Yochai; Goldhor, Omri; Gilad, Dani; Schcolnic, Tal; Leitner, Gabriel (Frontiers in Veterinary Science, 2023)
Introduction: The spread of antimicrobial resistance (AMR) is a major threat to human and animal health, and new solutions are needed to prevent a return to a world without effective antibiotics. Mastitis in dairy cows is a major reason for antimicrobial use in food animal production, and a possible source of AMR. In this study, acoustic pulse technology (APT) was explored as an alternative to antimicrobials for treatment of mastitis in dairy cows. In APT, mechanic energy is transmitted locally by soundwaves, fostering anti-inflammatory and angiogenic responses that promote udder recovery and enhance resistance to bacterial infections. Methods: We investigated 129 Israeli dairy cows with mastitis in a prospective, controlled study to assess the efficiency of APT treatment on cure and recovery rates. Defining suspected or confirmed infectious mastitis with clinical signs and/or somatic cell count (SCC) above 400,000 cells/mL, we divided animals into three groups: group 1 (n=29), cows with no bacterial findings (NBF); group 2 (n=82), cows with clinical signs of mastitis or SCC >400,000 cells/mL in the most recent test; group 3 (n=18), cows with chronic mastitis (two or more tests with SCC >400,000 cells/mL within three months). APT treatment was applied to all animals consisting of 400 pulses on two sides of the infected quarter, delivered in three treatments for three days. Cure was defined when bacteria were isolated before but not after treatment, and recovery as a decrease in SCC to less than 250,000 cells/mL in two of three post-treatment tests. Results and discussion: In group 2, cure and recovery rates were 67.1% and 64.6%, respectively, and were not significantly different between Gram-negative and Gram-positive infections. A similar recovery rate was found in NBF cows. Cure and recovery rates were significantly lower in cows with chronic mastitis (22.2 and 27.8%, respectively). Considering a national estimated prevalence of mastitis and cost of individual treatment, these findings suggest that APT can save up to $15,106/year in a 100-cow herd. APT should be further investigated as a viable and sustainable alternative to antimicrobial therapy for mastitis, offering economic benefits to dairy production and the possibility of preventing AMR.